1999
DOI: 10.1152/ajpheart.1999.276.6.h1868
|View full text |Cite
|
Sign up to set email alerts
|

Cardioprotective effects of KB-R7943: a novel inhibitor of the reverse mode of Na+/Ca2+exchanger

Abstract: The novel inhibitor of the reverse mode of the Na+/Ca2+exchanger (NCE) KB-R7943 (KB) was tested in isolated rat cardiomyocytes exposed to 80 min of simulated ischemia [substrate-free anoxia, extracellular pH (pHo) of 6.4] and 15 min of reoxygenation (pHo 7.4). At pHo 6.4, 20 μmol/l KB was required for complete inhibition of the reverse mode of NCE. Treatment with 20 μmol/l KB only during anoxia did not influence the onset of rigor contracture and intracellular pH (pHi) (monitored with 2′,7′-bis(2-carboxyethyl)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
75
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 81 publications
(82 citation statements)
references
References 28 publications
7
75
0
Order By: Relevance
“…1B. These oscillations were abolished by the application of 10 µM KB-R7943, a NCX reverse-mode inhibitor [15]. We have previously shown that KB-R7943 is highly selective for the reverse mode of NCX in the rabbit IVC [16].…”
Section: Simulationsmentioning
confidence: 90%
“…1B. These oscillations were abolished by the application of 10 µM KB-R7943, a NCX reverse-mode inhibitor [15]. We have previously shown that KB-R7943 is highly selective for the reverse mode of NCX in the rabbit IVC [16].…”
Section: Simulationsmentioning
confidence: 90%
“…Recently, the isothiourea derivative KB-R7943 has been shown to selectively inhibit the reverse mode of the Na ϩ -Ca 2ϩ exchanger. 38 KB-R7943 has been shown to prevent digitalis-induced calcium overload of cardiomyocytes 21 and was also effective in preventing reoxygenationinduced injury in cardiomyocytes 39 and isolated papillary muscles. 40 The data from the present study show that KB-R7943 could prevent hydroxyl radical-induced acute diastolic dysfunction.…”
Section: Hydroxyl Radicals and Calcium Overloadmentioning
confidence: 99%
“…In isolated rat cardiomyocytes exposed to simulated ischemia KB-R7943 reduced the [Ca 2 þ ] i overload and delayed the onset of the contracture (Ladilov et al, 1999). The raise in [Ca 2 þ ] i, induced by the removal of extracellular Na þ , was blocked by 90% in the presence of KB-R7943 (Tokuno et al, 2000).…”
Section: Introductionmentioning
confidence: 97%